Praktik Penghindaran Pajak di Indonesia - Sari Dewi (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the influence of Company Size and Corporate Social Responsibility (CSR) on the level of Tax avoidance in Indonesia. This study is a study with the population of companies listed on the IDX from 2017 to 2020. The sampling technique is Purposive sampling, andthe ata studied is secondary data, which is then tested by Multiple Linear Regression analysis. The Disclosure of Corporate Social Responsibility (CSR) towards Tax Avoidance of Public Companies in Indonesia is a social problem so that in paying taxes according to regulations must be done by the company. The results of the study that CSR does not affect tax avoidance, while company size, leverage and growth affect tax avoidance. Manufacturing enterprises of the consumer goods sector of the year 2017-2020.